Gender and the labor market: What have we learned from field and lab experiments? - Ghazala Azmat; Barbara Petrongolo (Queen Mary University of London, School of Economics and Finance, 2014)
We discuss the contribution of the experimental literature to the understanding of both traditional and previously unexplored dimensions of gender differences and discuss their bearings on labor market outcomes. Experiments have offered new findings on gender discrimination, and while they have identified a bias against hiring women in some labor market segments, the discrimination detected in field experiments is less pervasive than that implied by the regression approach. Experiments have also offered new insights into gender differences in preferences: women appear to gain less from negotiation, have lower preferences than men for risk and competition, and may be more sensitive to social cues. These gender differences in preferences also have implications in group settings, whereby the gender composition of a group affects team decisions and performance. Most of the evidence on gender traits comes from the lab, and key open questions remain as to the source of gender preferences -nature versus nurture, or their interaction - and their role, if any, in the workplace.
Keywords: J16; J24; J71; C91; C92; C93; 330; Gender; Field experiments; Lab experiments; Discrimination; Gender preferences